Graphical Access to Medical Expert Systems: II. Design of an Interface for Physicians - Lane, C. D.; Walton, Joan D.; Shortliffe, E. H. (Methods of Information in Medicine, 1986)
The ONCOCIN Interviewer program provides a graphical interface between physicians and an expert system that is designed to assist with therapy selection for patients receiving experimental cancer therapy. A principal goal has been to increase acceptance of advanced computer tools in a clinical setting. The interface has been developed for high-performance Lisp workstations and is tailored to the existing paper forms and practices of the outpatient clinic. To be flexible, the program makes use of a document formatting language to control a raster graphics display of medical forms, traditional paper versions of which have been used to track patient progress. The program utilizes a mouse input device coupled with a software-defined data entry approach that may be customized to the specific environment. The work described suggests ways in which high density graphics interfaces, with pointing devices rather than an emphasis on keyboards, may make decision support tools more useful to physicians and more acceptable to them.
Keywords: Document Formatting; Software Input Devices; Lisp Workstations; Human-Computer Interaction; Expert Systems